DDRE-14. HEMP DERIVED EXTRACELLULAR VESICLES (EVS): A POTENTIAL ANTI-GLIOMA THERAPY. (9th November 2020) - Azari, Hassan; Koopaei, Nasser Nassiri; Nouri, Mohammad-Zaman; Hall, Jesse D; Denslow, Nancy D; Schmittgen, Thomas D; Reynolds, Brent A
Abstract: INTRODUCTION: Extracellular vesicles (EVs) have been harvested from many plant sources, some of which have anti-cancer effects and some could be used as therapeutic nanodelivery vectors. Hemp plant is a natural source of cannabinoids, of which delta 9-tetrahydroxicannabinol (THC) and cannabidiol (CBD) have proven anti-cancer proprieties. HYPOTHESIS: We hypothesized that hemp EVs are enriched in cannabinoids and their application will reduce glioblastoma (GBM) tumor progression. APPROACH: EVs were isolated from the hemp plant using ultracentrifugation. Nanotracking analysis, electron microscopy and liquid chromatography tandem mass spectrometry (LC-MS/MS) were utilized to characterize EVs. GBM cell lines were cultured in the neuropshere assay to evaluate hemp EVs anti-glioma effects. Fluorescent-labelled EVs were used to evaluate their brain tissue distribution in orthotopic patient-derived GBM xenografts. RESULTS: Hemp EVs have a median diameter of 112.6nm with a typical lipid-bilayer structure. LC-MS/MS have shown that while cannabidiolic, cannabigerolic, and tetrahydroxicannabinolic acids represent 69.1 ± 2.1%, 19.1 ± 1.6%, 6.5 ± 0.54% of the total cannabinoids in hemp EVs, CBD and THC only make 4.75 ± 0.26%, and 0.5 ± 0.3%. Hemp EVs are potent anti-glioma agents with a 7-day LD-50 of 1.04µM and 2.4µM [based on EVs total cannabinoid content] for KR-158 and L0 GBM lines, respectively. Compared to the vehicle, overnight incubation of L0 cells with 1µM hemp EVs significantly reduced GBM cell migration (630.3 ± 61.43 vs 143.7 ± 8.7). Intranasal administration of hemp EVs led to a widespread distribution in tumor bearing brain including GBM tumor core. CONCLUSION: Based on these results, hemp EVs with enriched cannabinoid content exert antiglioma effect in-vitro and when delivered intranasally, are widely distributed throughout the brain and within the tumor of PDX animals. Further experiments are ongoing to address the impact of nasally-delivered hemp EVs on tumor progression and compare to the application of purified acidic cannabinoids.